Mechanism of the photoinduced uncaging reaction of puromycin protected by a 6-nitroveratryloxycarbonyl group - Kohl-Landgraf, Jörg; Lefrancois, Daniel; Mewes, Jan-Michael; Dreuw, Andreas (Journal of the American Chemical Society, 2014)
The cleavage of a photolabile nitroveratryloxycarbonyl protecting group, which is widely used as caging group, was studied by femtosecond transient absorption spectroscopy in the visible and infrared spectral range and by flash-photolysis experiments on the longer time scale. On the basis of quantum-chemical calculations it is shown that directly after excitation, triplet absorption that is not part of the reactive pathway dominates the transient spectrum and that the molecules following the triplet pathway are trapped in a nonreactive triplet state. By contrast, photolysis proceeds from the singlet manifold. Therefore, trapping in the triplet state lowers the quantum yield of the process for this compound compared with other o-nitrobenzyl protecting groups. With our integrated approach of time-resolved UV and IR measurements and calculations, we can characterize the entire uncaging mechanism and identify the most relevant intermediate states along the reaction pathway. The final uncaging is accomplished within 32 μs.